Determination of rimantadine in dosage form «Grippomix» using the ion-selective electrode - Andronchyk, Kseniya V.; Egorov, Vladimir V. (Journal of the Belarusian State University. Chemistry, 2017)
The possibility of direct potentiometric rimantadine determination in dosage form «Grippomix» using the ion-selective electrode (ISE) with the membrane based on tetrakis(4-chlorophenyl)borate (TCPB) as the ion-exchanger was investigated. It was shown that from all components of the dosage form only cetirizine can significantly influence on the electrode functioning. It was found that the replacement of o-phenyloctylether as the plasticizer by the tris(2-ethylhexyl) phosphate (TEHP) in the electrode membrane can reduce the influence of cetirizine almost in 30 times. The ISE membrane with 0.5 % of TCPB, 66.5 % of TEHP and 33.0 % of polyvinylchloride as the polymer matrix demonstrates the linear response to rimantadine in the concentration range 1 ⋅ 10–5–1 ⋅ 10–1 mol / l with the slope of electrode function close to the nernstian one (58.6 mV/decade at 20 °C), lower detection limit 6 ⋅ 10– 6 mol / l and retains operability for 6 months. Standard deviation of electrode potential in the 1 ⋅ 10–3 mol / l rimantadine solution is 0.33 mV. The pH variation from 2 to 9 do not affect at the ISEs response to rimantadine. On the other hand, the response to cetirizine cation depends on pH and at рН ≥ 3 it drastically reduces because of cetirizine transformation to electrode inactive zwitterion form. The influence of cetirizine on the rimantadine-selective electrode response is fully suppressed if analysis is carried out in phosphate buffer medium (pH 6.86). Standard solution method (one-point calibration) and limiting solutions method (two-point calibration) are proposed for direct potentiometric rimantadine determination. Both techniques are characterized by high reproducibility (Sr ≤ 0.6 %), precision estimated by the criterion «introduced/labeled – found» was no worse than 0.8 %.